Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.